Characterization of Bio-Oil and Bio-Asphalt Produced Through Catalytic Pyrolysis of Different Biomass Feedstocks - Dewajani, Heny; Irfin, Zakijah; Iswara, M. Agung Indra; Ramadhana, Rucita; Wahyudi, Moch. Ikhsan; Riris, Farikhatul Iza (Jurnal Teknik Kimia dan Lingkungan, 2025)
Asphalt is an aggregate binder in road pavement construction derived from the residue of the petroleum fractionation process, a non-renewable natural resource. Reliance on petroleum asphalt leads to resource scarcity and increased production costs. One alternative to reduce this dependence is the use of bio-asphalt substitutes, which utilize renewable natural resources derived from biomass. The abundance of biomass such as coconut shells, sawdust, and coffee husk in East Java, Indonesia, makes it a promising resource for bio-asphalt synthesis. This study analyzes the effect of biomass types and catalyst mass ratios on the characteristics of bio-asphalt from bio-oil pyrolysis and its mixture with petroleum asphalt, specifically the penetration (pen) 60/70. The research stages include biomass preparation, zeolite catalyst activation, biomass pyrolysis into bio-oil, evaporation into bio-asphalt, and mixture analysis. Optimal characteristics were achieved using a 6% w/w coconut shell biomass catalyst, resulting in a bio-oil yield of 47.27% and a density of 1.060 g/mL. The bio-asphalt yield was 3.41% when mixed with petroleum asphalt pen 60/70. The bio-asphalt exhibited a penetration value of 66.35, a softening point of 52°C, and a density of 1.042 g/cm³, in accordance with the Indonesian National Standard (SNI) 8135:2015.